Organizational Commitment as an Intervening Variable in the Effect of Empowerment, Incentives and Self Efficacy on Employee Performance - Dewi, Ni Luh Ayu Trisna; Martini, Ida Ayu Oka (Pusat Publikasi Nusantara, 2024)
Badan Kepegawaian Negara (BKN) are an organization of government agencies operating in the field of public service with a unique context as well as regulations and policies on public service management. The high performance of officials is crucial to government agencies. Staff performance is a qualitative and quantitative measure of work performance and work outcomes based on the standard of work achieved by employees per unit of time in performing work in accordance with the assigned responsibilities. The study aims to look at the impact of empowerment, incentives, self-effectiveness, and organizational commitments on staff performance, the influence of empowering, incentive, and self effectiveness in relation to organization commitments, as well as the effect of empoverment, motivation, and Self-effictiveness on employee performance with the intervening variable of organizational engagement. This is a quantitative descriptive study, with respondents of 90 BKN employees, using questionnaires as a basis for data assumption as well as data analysis using SmartPLS software. The results of the analysis show that empowerment, incentives, self efficacy, and commitment of the organization have a positive and significant impact on the performance of the staff, the influence of empowering, incentive, and self effecacy have a significant and positive effect on the organization's commitment, and empowerement, the incentive has an impact on staff's performance with the commitment organiassi as a variable part mediation, and the self efficiency on staff performance with organizational commitmentasi as a full mediation variable.